Social Services for Older Persons in Residential Care: A Journal-Style Analysis of Service Effectiveness at UPTD BPSLUT “Senja Cerah”, North Sulawesi, Indonesia - Aminah Ruyani; Ferdinand Kerebungu; Julien Biringan (JR Education, 2026)
The study examines the effectiveness of residential social services focused on the fulfillment of decent living needs for older persons and identifies supporting and inhibiting factors in service delivery. Using a qualitative descriptive design, the original research collected data through interviews, observation, and documentation involving managers, section heads, staff, health workers, and older residents as service recipients. The research interprets the findings through public administration, public service management, elderly social service, and social rehabilitation assistance frameworks. The findings show that services are present and meaningful, but their effectiveness remains partial. Procedures exist and are understood by staff, yet administrative flexibility, limited home visits, and incomplete operational resources weaken consistency. Staff display commitment and initiative, but the absence of dedicated caregivers creates role overload and leaves residents dependent on mutual help. Service time is generally organized through schedules, but health checks, recreation, and some rehabilitation activities remain irregular because of limited medicine, budget, and personnel. Facilities include dormitories, a hall, a clinic, a kitchen, and residential infrastructure, but they are not yet fully elderly-friendly, particularly in relation to handrails, accessible pathways, and bathrooms. Supporting factors include staff commitment, improvisation, partnerships with educational institutions, visits from community and religious groups, and external donations. Inhibiting factors include limited human resources, limited budget, and limited authority of the UPTD over rehabilitation spending. The research argues that elderly social care must be understood not merely as routine custodial service, but as a humanistic public service requiring clear standards, adequate caregivers, elderly-friendly infrastructure, and multi-actor collaboration. The study contributes to public administration scholarship by showing how service quality for vulnerable citizens depends on the intersection of procedure, frontline discretion, resources, and social care ethics.